Comparison of Oxidant and Antioxidant Parameters in Patients with Sjögren’s Syndrome and Healthy Subjects - Dogan, İsmail; Erten, Sukran; Sahin, Ali; Isıkoglu, Semra; Neselioglu, Salim; Ergin, Merve; Erel, Ozcan (Aktuelle Rheumatologie, 2020)
Objective Oxidative stress may have an effect on the pathogenesis of diseases, including autoimmune rheumatic diseases. We aimed to investigate the serum paraoxonase activity and other oxidant/antioxidant parameters in patients with Sjögren’s syndrome (SS) and healthy controls.Methods 85 patients with SS and 65 healthy subjects were included in the study. Groups were age and gender-matched and had no liver disease. Serum paraoxonase (PON)-1 activity, stimulated paraoxonase (SPON), PON-1 phenotypes that represent polymorphism (Q192R; QQ, QR, RR), arylesterase (ARE), total oxidant status (TOS), total antioxidant capacity (TAC), oxidative stress index (OSI), advanced oxidative protein products (AOPP), total thioles (TTL) and ischaemia-modified albumin (IMA) were measured in all study participants.Results Statistically significant differences were found in the QQ and QR+RR phenotype of PON-1 for TAC, TOS and TTL (p<0.001) between SS and healthy groups. The other parameters were statistically insignificant.Conclusion Antioxidant parameters were lower in SS patients compared with healthy controls. Conversely, oxidant parameters were higher. This imbalance may play a role in SS pathogenesis.Ziel Oxidativer Stress kann die Pathogenese von Krankheiten, einschließlich rheumatischer Autoimmunerkrankungen, beeinflussen. Wir wollten die Paraoxonase-Aktivität im Serum und andere oxidative / antioxidative Parameter bei Patienten mit Sjögren-Syndrom (SS) und gesunden Kontrollpersonen untersuchen.Methode 85 Patienten mit SS und 65 gesunde Probanden wurden in die Studie eingeschlossen. Die Gruppen waren alters- und geschlechtsgleich und hatten keine Lebererkrankungen. Bei allen Studienteilnehmern wurden Serum-Paraoxonase (PON) 1-Aktivität, stimulierte Paraoxonase (SPON), PON 1-Phänotypen, die Polymorphismus darstellen (Q192R; QQ, QR, RR), Arylesterase (ARE), Gesamtoxidationsstatus (TOS), Gesamtantioxidationskapazität (TAC), oxidativer Stress-Index (OSI), fortgeschrittene oxidative Proteinprodukte (AOPP), Gesamtthiole (TTL) und Ischämie-modifiziertes Albumin (IMA) gemessen.Ergebnisse Es gab statistisch signifikante Unterschiede im QQ- und QR+RR-Phänotyp von PON-1 für TAC, TOS und TTL (p<0,001) zwischen SS- und gesunden Gruppen. Die anderen Parameter waren statistisch nicht signifikant.Schlussfolgerung Die Antioxidationsparameter waren bei SS-Patienten im Vergleich zu gesunden Kontrollen niedriger, und umgekehrt waren die Oxidationsparameter höher. Dieses Ungleichgewicht kann eine Rolle bei der SS-Pathogenese spielen.
Keywords: Oxidant/antioxidant status; paraoxonase; Sjögrenʼs syndrome